Assessing Micromobility Users’ Knowledge of Regulations: Valencia (Spain) Case Study - Alejandra Sofía Fonseca-Cabrera; David Llopis-Castelló; Ana María Pérez-Zuriaga; Alfredo García (Safety)
Micromobility is a current and growing integrated transport mode that has its own regulations and requirements for riding. In this context, bicycle usage has been regulated years before. However, the coexistence with new micromobility vehicles, such as e-scooters, has generated the necessity of the development of additional regulatory frameworks. Administrators and technicians have been working for the last 7 years on this aspect. However, a proper evaluation from the user perspective has not been carried out. Thus, there is a need to identify whether micromobility users are aware of the regulations that they must comply with. This research has analyzed the users’ knowledge through a survey, a transport-typical data collection method, but used implicitly as an evaluation, where a score was obtained per user. As a result, the average score obtained was 4.5, reflecting an insufficient qualification. Additionally, statistically significant differences were found between the average score obtained between cyclists and personal mobility vehicle (PMV) users, as well as mean differences between age, micromobility vehicle, ownership, and holding a driver’s license. In conclusion, a new gap has been found in relation to micromobility users’ behavior that has to be addressed.